The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/2177-6709.25.1.036-046.oar
|View full text |Cite|
|
Sign up to set email alerts
|

Orthodontic management of a non-syndromic patient with concomitant bimaxillary hypohyperdontia: a case report

Abstract: Introduction: Tooth agenesis is one of the most common dental anomalies; however, the concomitant occurrence of opposite dental numerical variation of hypohyperdontia is extremely rare. Objective: To report the successful orthodontic management of a patient with non-syndromic concomitant bilateral agenesis of mandibular canines and two midline inverted supernumerary maxillary teeth. Case report: 21-year-old female patient with a chief complaint of protrusive right maxillary central incisor. The patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although there are not many publications on the subject in the literature, we found a wide range of approaches, but each of them emphasizes the complex variety of problems that are concomitant: a difficult eruption of adjacent teeth, dental transposition, conditions for tooth retention, root resorption of teeth, ectopic breakthrough and others [11]. Therefore, the publication of each new case enriches the orthodontic community with a new clinical approach or confirms one.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although there are not many publications on the subject in the literature, we found a wide range of approaches, but each of them emphasizes the complex variety of problems that are concomitant: a difficult eruption of adjacent teeth, dental transposition, conditions for tooth retention, root resorption of teeth, ectopic breakthrough and others [11]. Therefore, the publication of each new case enriches the orthodontic community with a new clinical approach or confirms one.…”
Section: Discussionmentioning
confidence: 87%
“…In our previous study, we found out that the prevalence of the supernumerary teeth is 1.82%, and the prevalence of mesiodens is 0.74% [10]. Exactly in the same area, hyperodontia is observed in concomitant hypo-hyperodontia [11,12,13]. Hyperodontia in the frontal segment drastically changes the position of the teeth and leads to occlusal disorders.…”
Section: Introductionmentioning
confidence: 99%